2018
DOI: 10.1002/adma.201706758
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Coordinated Single Cobalt Atom Catalysts for Oxygen Reduction in Proton Exchange Membrane Fuel Cells

Abstract: Due to the Fenton reaction, the presence of Fe and peroxide in electrodes generates free radicals causing serious degradation of the organic ionomer and the membrane. Pt-free and Fe-free cathode catalysts therefore are urgently needed for durable and inexpensive proton exchange membrane fuel cells (PEMFCs). Herein, a high-performance nitrogen-coordinated single Co atom catalyst is derived from Co-doped metal-organic frameworks (MOFs) through a one-step thermal activation. Aberration-corrected electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
650
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 841 publications
(695 citation statements)
references
References 61 publications
26
650
2
3
Order By: Relevance
“…As shown by the HAADF‐STEM images and EDX mapping results, the Co, Ni, and Mn single atoms with high concentration were uniformly distributed on the HCF (Figure 4b–d,g–i,l–n). The binding energies of Co, Ni, and Mn in XPS spectra were similar with those of the previously reported Co‐N‐C, Ni‐N‐C, and Mn‐N‐C single atoms (Figure 4e,j,o), respectively . Determined by the XPS results, the mass percentage of Co, Ni, and Mn single atoms were calculated to be 3.7%, 4.2%, and 2.6%, respectively (Figure S16 and Table S4, Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…As shown by the HAADF‐STEM images and EDX mapping results, the Co, Ni, and Mn single atoms with high concentration were uniformly distributed on the HCF (Figure 4b–d,g–i,l–n). The binding energies of Co, Ni, and Mn in XPS spectra were similar with those of the previously reported Co‐N‐C, Ni‐N‐C, and Mn‐N‐C single atoms (Figure 4e,j,o), respectively . Determined by the XPS results, the mass percentage of Co, Ni, and Mn single atoms were calculated to be 3.7%, 4.2%, and 2.6%, respectively (Figure S16 and Table S4, Supporting Information).…”
Section: Resultssupporting
confidence: 85%
“…[28,54,121] However,s urpassing the efficiencyo fP t/C is challenging since the reaction proceeds by a2e À pathway and produces less electricity than the alternative 4e À pathway.On the other hand, this presents an efficient route for the H 2 O 2 synthesis,i nw hich case higher selectivity is expected upon complete elimination of NPs and clusters.T he improved performance of aPt 1 /TiC catalyst than Pt 1 /TiN indicated that the support can strongly influence the performance. [122][123][124][125][126][127] Interesting prospects to tune the mechanism have been reported in the oxidations of methanol, ethanol, and formic acid. [122][123][124][125][126][127] Interesting prospects to tune the mechanism have been reported in the oxidations of methanol, ethanol, and formic acid.…”
Section: Electrocatalysismentioning
confidence: 99%
“…Figure 3d displays an obvious OER activity (E OER10 = 1.58 V), almost identical to that of Ir/C (1.56 V). [23] N-HC@G-900 shows lower acidic stability than Ir/C (Figure 3e), but better than other reported metal-free electrocatalysts. [23] N-HC@G-900 shows lower acidic stability than Ir/C (Figure 3e), but better than other reported metal-free electrocatalysts.…”
Section: Zuschriftenmentioning
confidence: 74%